Smoking water-pipe, chewing nass and prevalence of heart disease: a cross-sectional analysis of baseline data from the Golestan Cohort Study, Iran. Issue 4 (20th December 2012) - Islami, Farhad; Pourshams, Akram; Vedanthan, Rajesh; Poustchi, Hossein; Kamangar, Farin; Golozar, Asieh; Etemadi, Arash; Khademi, Hooman; Freedman, Neal D; Merat, Shahin; Garg, Vaani; Fuster, Valentin; et al.
Abstract : Objective: Water-pipe and smokeless tobacco use have been associated with several adverse health outcomes. However, little information is available on the association between water-pipe use and heart disease (HD). Therefore, we investigated the association of smoking water-pipe and chewing nass (a mixture of tobacco, lime and ash) with prevalent HD. Design: Cross-sectional study. Setting: Baseline data (collected in 2004–2008) from a prospective population-based study in Golestan Province, Iran. Participants: 50 045 residents of Golestan (40–75 years old; 42.4% men). Main outcome measures: ORs and 95% CIs from multivariate logistic regression models for the association of water-pipe and nass use with HD prevalence. Results: A total of 3051 (6.1%) participants reported a history of HD, and 525 (1.1%) and 3726 (7.5%) reported ever water-pipe or nass use, respectively. Heavy water-pipe smoking was significantly associated with HD prevalence (highest level of cumulative use vs never use, OR=3.75; 95% CI 1.52 to 9.22; p for trend=0.04). This association persisted when using different cut-off points, when restricting HD to those taking nitrate compound medications, and among never cigarette smokers. There was no significant association between nass use and HD prevalence (highest category of use vs never use, OR=0.91; 95% CI 0.69 to 1.20). Conclusions: Our study suggests a significant association between HD and heavy water-pipe smoking. Although the existing evidence suggesting similar biological consequences of water-pipe and cigarette smoking make this association plausible, results of our study were based on a modest number of water-pipe users and need to be replicated in further studies.